2020
DOI: 10.1111/ele.13460
|View full text |Cite
|
Sign up to set email alerts
|

The rescue effect and inference from isolation–extinction relationships

Abstract: The rescue effect in metapopulations hypothesises that less isolated patches are unlikely to go extinct because recolonisation may occur between breeding seasons (‘recolonisation rescue’), or immigrants may sufficiently bolster population size to prevent extinction altogether (‘demographic rescue’). These mechanisms have rarely been demonstrated directly, and most evidence of the rescue effect is from relationships between isolation and extinction. We determined the frequency of recolonisation rescue for metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Decades of ecological theory on risk spreading in spatially structured populations shows how variability in the contribution of separate subpopulations can deliver net benefits for metapopulation growth and persistence (25)(26)(27)(28). In general, more subpopulations and greater population connectivity reduce the probability of local extinctions via a "rescue effect" and dampen local fluctuations in population replenishment (29)(30)(31)(32) and fishery catches (33,34). If correct, effective networks of no-take marine reserves could mitigate against the volatility of larval supply provided the network can dampen the spatially and temporally variable contributions of individual reserves (20,21).…”
mentioning
confidence: 99%
“…Decades of ecological theory on risk spreading in spatially structured populations shows how variability in the contribution of separate subpopulations can deliver net benefits for metapopulation growth and persistence (25)(26)(27)(28). In general, more subpopulations and greater population connectivity reduce the probability of local extinctions via a "rescue effect" and dampen local fluctuations in population replenishment (29)(30)(31)(32) and fishery catches (33,34). If correct, effective networks of no-take marine reserves could mitigate against the volatility of larval supply provided the network can dampen the spatially and temporally variable contributions of individual reserves (20,21).…”
mentioning
confidence: 99%
“…Our study, however, included many more freshwater fish species and considered a decadal scale. These findings are highly supportive of the rescue effect (Gotelli, 1991; Hanski, 1982), where immigration of individuals from surrounding populations decreases the extinction probability of a local population (Brown & Kodric‐Brown, 1977; Gotelli & Kelley, 1993; Schmidt & Beissinger, 2020). Although supported by theoretical models (Freckleton et al., 2005; Hanski, 1982), empirical evidence for the rescue effect decreasing regional and local extinction probabilities are somewhat divergent: while some early metapopulation studies have not found a strong correlation between the fraction of sites occupied and extinction probabilities (Gotelli & Kelley, 1993; Gotelli & Taylor, 1999b; Pfister, 1998), others have suggested that there is an effect (Dornier & Cheptou, 2012; Sutherland, Elston & Lambin, 2012; Bergerot et al., 2013; Vergara et al., 2016; Omar et al., 2019).…”
Section: Discussionmentioning
confidence: 70%
“…These authors found that the fraction of sites occupied was dependent on the flood cycle, and rivers could function as a source of propagules for lakes. The rescue effect may also be influenced by habitat patch variables such as isolation, area, and habitat quality for a given species (Penha et al., 2019; Schmidt & Beissinger, 2020; Schuler et al., 2017). Although environmental variability could potentially influence patterns of local persistence differently for each species, the regularity of mean landscape occupancy and local abundance as important predictors in our cross‐species comparisons across lakes with different areas, connectivity, and environmental variability consistently points to the importance of the rescue effect on local population persistence in this floodplain.…”
Section: Discussionmentioning
confidence: 99%
“…Larger islands support more individuals, and this is generally coupled with higher species richness (Palmer & White, 1994;Wright, 1983). Species population sizes and immigration rates also increase with island area (Brown & Kodric-Brown, 1977), both leading to decreasing extinction risks and hence to higher species richness (Van Schmidt & Beissinger, 2020). Species diversity on islands is, thus, maintained by random immigration and extinction dynamics that change with area, with larger islands having higher species diversity than smaller ones (MacArthur & Wilson, 1967).…”
Section: Introductionmentioning
confidence: 99%